Pengaruh Budaya organisasi dan Kompensasi terhadap Komitmen organisasi melalui Motivasi kerja pada Karyawan Hotel Halogen Sidoarjo - Enrico Satria Nugraha (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This research proposes to explain the effect of organizational culture and compensation on organizational commitment through work motivation. This research is quantitative, with 38 respondents, using purposive sampling to collect data from X Hotel employees. The analysis technique used in this study is the Structural Equation Modelling Partial Least Square with PLS software version 4.0. The results obtained from this research show that Organizational culture and compensation have a positive effect on work motivation and organizational commitment, work motivation have a positive impact on organizational commitment, and also work motivation can mediate the influence of organizational culture on organizational commitment. Meanwhile, work motivation can’t mediate the influence of compensation on organizational commitment. The leaders of X Hotel need to hold intimate activities outside the city for more open relationships between management and employees. Hotel leaders need to guide and direct employees to encourage them to have a courageous attitude in decision-making. Hotel leaders should show appreciation to employees for their excellent performance by giving bonuses or recognition. Training and educational activities are needed for Hotel employees to enhance their skills and make them more competitive. Furthermore, organizing team-building activities for all members of Halogen Hotel in Sidoarjo can help strengthen the relationship between leaders and employees.